Curriculum reconstruction in Islamic schools: A pedagogical framework for recontextualizing Islamic knowledge - Ahmad Dwi Nur Khalim; Handaru Baskara Aji; Ahmad Lukman Fahmi; Muhammad Masykuri Latif; Adib Rubiyad (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2026)
Purpose - Research on Islamic curriculum has largely focused on instructional innovation and curriculum implementation, with limited attention to how Islamic knowledge is reconstructed into meaningful learning experiences. This study develops and empirically examines BERVAKONTA as a Curriculum Reconstruction Framework for Aqidah Akhlak education in Islamic junior secondary schools.Design/methods/approach - An Educational Design Research (EDR) approach integrated with a qualitative case study design was employed. The study comprised four phases: needs analysis, conceptual reconstruction, curriculum configuration analysis, and conceptual synthesis. Data were collected through classroom observations, semi-structured interviews, and document analysis, and analyzed iteratively using interactive qualitative analysis.Findings - The findings reveal that the main challenge of Aqidah Akhlak education lies in the organization of Islamic knowledge rather than curriculum content. Curriculum reconstruction integrates meaningful learning, value orientation, contextual engagement, and authentic application into a coherent learning trajectory linking learning outcomes, content, activities, assessment, and character formation. This process resulted in the BERVAKONTA Curriculum Reconstruction Framework, which explains the pedagogical mechanism for transforming Islamic knowledge into integrated learning experiences.Research implications/limitations - The framework provides a conceptual basis for curriculum reconstruction in Islamic education. As the study was conducted in a single Islamic junior secondary school, further validation across different subjects and educational contexts is required.Originality/value - This study positions BERVAKONTA as a Curriculum Reconstruction Framework, offering a theoretical contribution to Islamic Curriculum Studies by explaining how knowledge, values, context, and authentic practice are systematically integrated into meaningful learning experiences.